Food Composition and Preference of Captive Javan Langur (Trachypithecus auratus) in Gembira Loka Zoo, Yogyakarta - Eunnike Adelina; Laurentia Henrieta Permita Sari Purba; Vinsa Cantya Prakasita (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Javan langur (Trachypithecus auratus) is one of the endemic primate species of Indonesia. Its populations were exposed to extinction risk caused by human activities. Thus, conservation efforts such as ex-situ conservation were needed to preserve this species. One of the javan langur ex-situ conservation in Yogyakarta is the Gembira Loka Zoo. In captivity, animals must be guaranteed to be free from hunger and stay nourished. One aspect to support this welfare is food supply. Therefore, this study aimed to identify the food composition and analyze the correlation between food preference and feeding duration of each food item group. We used scan animal sampling method with five minutes intervals to observe the behavior of seven individuals of captive javan langurs. The result showed that there are three groups of food (fruit, vegetable, and leaf) provided daily to javan langurs in Gembira Loka Zoo. All the individuals spent most their time to consumed food from vegetable group, except for infant female who had the highest duration in the leaf group. In addition, based on which food they consumed first every feeding time (preference food), javan langurs preferred vegetable over fruit and leaf. Based on the Spearman correlation test, there are positive correlations of duration and preference of feeding except for leaf groups. This result was different from the natural food composition of javan langurs which mostly consisted of leaves. This study might help the zoo to consider the food items provided for the animals to increase animal welfare.